E-Commerce: A Study On Internet Shopping In Malaysia - Omar, Ghazali (2000)
This study aims to establish a preliminary assessment, evaluation and understanding of the characteristics of Internet shopping in Malaysia. The findings from the study will provide useful input for the development of Internet shopping in Malaysia.